Household Food Insecurity Negatively Affects Multiple Facets of Well-Being for Those Living in Slums and Informal Settlements. (14th June 2022) - Boateng, Godfred; Adams, Ellis
Abstract: Objectives: Household food insecurity has been associated with deleterious consequences on the physical health of vulnerable populations. However, few studies have examined its effect on the individual facets of well-being in slums and informal settlements. Therefore, this study examined (1) the effect of food insecurity on the intellectual, spiritual, and psychological well-being and (2) the effect of food insecurity on life satisfaction among the urban poor. Methods: Data for this study were collected from three slums in Ghana (N = 1, 033). The key independent variable, food insecurity was assessed using household food insecurity access scale (HFIAS); we then assessed intellectual (using a scale of 7 items), spiritual (Spiritual Well-Being Index), and psychological (WHO-5 Well-Being Index) well-being and life satisfaction (satisfaction with life scale) for the outcome variables. Many covariates were assessed, including, housing insecurity (Multilevel Multidimensional Housing Insecurity Scale), neighborhood health (neighborhood safe scale), poverty (less than $5.50 a day), stress (perceived stress scale), and socio-demography. Following descriptive and bivariate analyses, we built multivariable models for each of the outcome measures by including all covariates significant at p < 0.05. We assessed the effect of food insecurity on all four outcome measures using Poisson regression. Results: In the bivariate models, food insecurity decreased the rate ratios for intellectual (IRR = .99, P < .001), spiritual (IRR = .99, p < .001), and psychological (IRR = .96, p < .001) well-being, as well as life satisfaction (IRR = 0.98, p < .001). In the multivariable models, food insecurity decreased the rate ratios of intellectual, spiritual, and psychological well-being by .99, .99, and .98 factors, respectively. Poverty and stress were associated with decreased rate ratios on all four outcome measures. However, neighborhood health and psychological well-being increased the rate ratios of life satisfaction. Conclusions: These data show that food insecurity is a significant predictor of poor intellectual, spiritual, and psychological well-being among slum dwellers. Funding Sources: This work was supported by a Pilot Project Grant at the University of Texas at Arlington and the Keough School of Global Affairs at the University of Notre Dame.